2015
DOI: 10.1007/s00464-015-4712-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endoscopically inserted self-expandable metal stents in malignancy according to the type of stent and the site of obstruction

Abstract: SEMS selection for malignant obstruction of the upper gastrointestinal tract depends on the site of obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…One retrospective study included 15 patients with Billroth‐II anastomosis (11%), and another one included 18 patients with anastomotic obstruction (7.1%) . In two retrospective studies, both partially and fully covered types were used as covered SEMS …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One retrospective study included 15 patients with Billroth‐II anastomosis (11%), and another one included 18 patients with anastomotic obstruction (7.1%) . In two retrospective studies, both partially and fully covered types were used as covered SEMS …”
Section: Resultsmentioning
confidence: 99%
“… In the study by Woo et al ., covered SEMS included 21 fully covered SEMS (Niti‐S enteral). In the study by Jung et al ., covered SEMS included 16 fully covered SEMS. All other covered SEMS in the current meta‐analysis were partially covered. …”
Section: Resultsmentioning
confidence: 99%
“…48 The use of more permanent materials such as polytetrafluoroethylene (PTFE) or nylon has reduced this problem. 48, 49 Jang et al 48 reported an incidence of tumor overgrowth of 0.8% with the use of a dual stent covered with a nylon membrane with tumor obstruction occurring later after and more commonly in the duo- denal region. Some studies support that the use of chemotherapy after stent placement is associated with improved stents patency, 31,40 while others 50 studies show that it does not improve stent patency in patients with malignant GOO.…”
Section: Stent Dysfunctionmentioning
confidence: 99%
“…7,9,26 Migration is much higher in fully covered braided stents, reported in up to 38% to 56% 7,26 and historically bare stents have been preferred. The membrane of double knitted or modular construction does not extend to the stent ends, allowing the bare metal to impress into the bowel mucosa.…”
Section: Stent Failure Stent Migrationmentioning
confidence: 99%
“…The trade-off between the two primary modes of stent failure of stent occlusion by tumor ingrowth into bare metal stents and migration of fully covered stents have traditionally been reported as similar, ranging between 30% and 40% and increasing with survival. [5][6][7][8] Newer stent designs have tried to combine the anchoring capability of a bare stent with an additional membrane applied to the inside of the stent. Designs pursued currently, include metal stents where the membrane is sandwiched between two layers of metal and stents inserted as separate coaxial modules.…”
Section: Introductionmentioning
confidence: 99%